Concerning Possible Trends in Raising Effectiveness of Finance Policy of State - D. A. Dinets (Вестник Российского экономического университета имени Г. В. Плеханова)
The goal of the article is to substantiate parameters of monetary-credit and budget-taxation policy, which ensure extended reproduction on a scale of national economy. To attain this goal the following steps were taken: analysis of theoretical and applied aspects of mutual impact of monetary-credit and budget-taxation policy on parameters of macro-economic dynamics; investigation of reasons for low efficiency of transmission mechanism of monetarycredit policy; an attempt to explain causes of low efficiency of channels in transmission mechanism in view of present geo-political situation; proposal of the author’s approach to creating preconditions for eliminating antagonism between monetary-credit and budget-taxation policy in view of economic growth provision. The principle conclusion of the author implies the necessity to take into account the market volume formed by efforts of monetary-credit and budget-taxation authorities in coordination of parameters of monetary-credit and budget-taxation policy.